Kajian Sebaran Panas Permukaan Daratan Dengan Teknik Penginderaan Jauh Berbasis Cloud : Cloud-Based Remote Sensing Techniques for the Study of Land Surface Heat Distribution - Yusuf Aguswan; Petrisly Perkasa; Hari Prakasa; Glen Wildodo; Septian Adji Nugroho (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
Climate change is constant. The average temperature has risen since the globe was encased in ice millions of years ago. Current climate change is caused by natural events and human behavior in treating and managing the environment. The huge burning of coal, oil, and wood and deforestation caused by economic development has seriously damaged the world's climate. Global climate change may alter peat carbon stored by forest and land fires. Human activities like plantation development, agriculture, and logging have made tropical peatlands more vulnerable to fire. Indonesia has 44 million hectares of tropical peatlands, with 45% and 64% carbon content. This study addresses Palangka Raya's intermittent land surface heating. The Palangka Raya University academic community conducted this research to provide input on climate change and the global environment and to predict a symptom or occurrence that harms society. This project is part of the University of Palangka Raya's Principal Scientific Pattern (PIP): Science and Technology Innovation in Tropical Peat Swamp Areas and River Streams.